“Ahora, cansado el cuerpo”. Exceso de vida en Diario de una vida breve de Juan Manuel Silvela Sangro - Alías, Antonio (Studia Romanica Posnaniensia, 2024)
During almost ten years, between 1949 and 1958, Juan Manuel Silvel Sangro writes a series of notebooks that cover this period of absolute rest that he experiences following the diagnosis of a rare congenital heart disease. This writing exercise originates the posthumously edited Diario de una vida breve (1967), a melancholic record of the convalescent everyday life, where life is barely rooted in the diary’s time, whilst it seeks a kind of salvation. Even though Silvela Sangro’s life could be considered a failed one, he presents it as being “complete”, insofar its textual representation is permeated by a series of specific qualities: ‘passivity’, seen as a mode of existence that opens up the opportunity of confession in front of the ‘ontological helplessness’ (Zambrano); inoperosità, understood as a supreme happiness in the ethical exercise of self-contemplation and recognition (Spinoza/Agamben); and ‘care of the self’ as a practice of freedom, that, through intimate writing, points to the process of subjectivation (Foucault). The paper is based on these premises retrieved from the field of the contemporary “philosophy of life,” which indicate the complex relationship between ‘life’ and ‘writing’; a relation that Silvela Sangro codifies in the ‘(im)potence’ of his diary as vitae forma to suspend the illness and death.